미숙아에서 장막층의 섬유 끈에 의한 선천적 위 출구 폐쇄 1례 - 양소민; 은호선; 이순민; 장혜경; 박국인; 남궁란 (Perinatology (Online), 2014)
신생아에서 구토와 복부 팽만과 같은 위 출구 폐쇄 증상을 보이는 경우는 선천성 해부학적 이상이 있는 경우가 대부분이다. 선천적 위 출구 폐쇄를 일으키는 구조적 이상들은 그 위치와 폐쇄 정도에 따라 구분되어 왔다. 저자들은 지속적인구토와 상복부 팽만을 보인 미숙아에서 기존의 알려진 선천적 위 출구 폐쇄의 구분에서 벗어나는 장막층의 섬유 끈으로 인한 위 출구 폐쇄 1례를 경험하였기에 보고하는 바이다. Most of the gastric outlet obstruction symptoms like vomiting and abdominal distension were caused bycongenital anatomical abnormality in a neonate. Abnormal structures associated with congenital gastricoutlet obstruction have been categorized by its site and extent of obstruction. We report one case of persistingvomiting in a premature infant caused by serosal fibrous band in gastric outlet lesion, excluded from thecategory of congenital gastric outlet obstruction. KCI Citation Count: 0